The dealmaker's ten commandments : ten essential tools for business forged in the trenches of Hollywood - Cohen, Jeff B. (Jeffrey Bertan), 1974- (American Bar Association, 2015)
The Dealmaker's Ten Commandments provides a practical, no-nonsense methodology for negotiating deals, managing your time and handling crisis, all at the highest level. Authored by prominent transactional attorney and former child actor, Jeff B. Cohen, created The Dealmaker's Ten Commandments to overcome resistance and achieve his goals without losing his soul along the way. Although developed in Hollywood, the real world tactics, strategies and guiding principles are vital for any business environment.